Individualized Homeopathic Management of Grade II Hemorrhoids: A Case Report (Homoeopathy for All, 2025)
Background: Hemorrhoids are  a common anorectal condition  resulting from the pathological  enlargement and distal displacement  of anal vascular cushions.  Conventional treatments vary  from conservative management to  surgical intervention. Individualized  homeopathic prescribing is  frequently used in clinical practice  for symptomatic relief and long term management. Case Summary: A 45-year-old  female presented with chronic  constipation, painful defecation,  marked straining, and bleeding  per rectum for several months.  Examination indicated Grade II  internal hemorrhoids. The patient  also reported congestion of the  pelvic region, a sensation of  incomplete evacuation, and severe  rectal pain following stool. Based on  a detailed case analysis, Collinsonia  canadensis was prescribed in its  individualized potency. Results: Significant improvement  in pain, bleeding, and straining was  observed within two weeks. Follow up over three months showed  complete resolution of symptoms  and normalization of bowel habits  without recurrence. Conclusion: This case demonstrates  the potential role of individualized  homeopathic prescribing—specifi cally Collinsonia canadensis—in  the management of Grade II hemor rhoids. Further studies with larger  sample sizes are recommended.
Keywords: Hemorrhoids; Homeop athy; Collinsonia canadensis; Constipation; Case report